2021
DOI: 10.1002/acm2.13321
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in tumor subregion analysis based on medical imaging: A review

Abstract: Medical imaging is widely used in the diagnosis and treatment of cancer, and artificial intelligence (AI) has achieved tremendous success in medical image analysis. This paper reviews AI-based tumor subregion analysis in medical imaging. We summarize the latest AI-based methods for tumor subregion analysis and their applications. Specifically, we categorize the AI-based methods by training strategy: supervised and unsupervised. A detailed review of each category is presented, highlighting important contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 176 publications
0
12
0
Order By: Relevance
“…In addition to ve supervised machine learning algorithms, we subjected our ow cytometry-derived dataset (the standardized training dataset) to two unsupervised clustering algorithms (k-means clustering and Gaussian mixture clustering) in parallel 33 . As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ve supervised machine learning algorithms, we subjected our ow cytometry-derived dataset (the standardized training dataset) to two unsupervised clustering algorithms (k-means clustering and Gaussian mixture clustering) in parallel 33 . As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropilins are the transmembrane glycoproteins mainly located in the growing neurons which help in neuron development. Neuropilin 1 (NRP1) and neuropilin 2 (NRP2) are the receptors of class III semaphorin receptors and are also targeted by several ligands responsible for angiogenesis (Lin et al 2021). Neuropathological analysis with Covid-19 autopsies has revealed that cleaved S protein interacts with NRP1 and NRP2, which in-turn help the virus to infect the nervous system of the human being (Daly et al 2020;Cantuti-Castelvetri et al 2020).…”
Section: The Basic Mechanism Of Entrymentioning
confidence: 99%
“…To remedy this, convolutional neural networks (CNNs) have been employed to automate the segmentation task. [8][9][10][11] In this study, we propose a novel deep learning-based method to automatically segment the prostate and DILs on MRI for DIL dose boosting radiation therapy. This article is a continuation of our previous conference paper.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, simple intensity‐based image segmentation methods would be inefficient in distinguishing the specific DILs in MRI. To remedy this, convolutional neural networks (CNNs) have been employed to automate the segmentation task 8–11 …”
Section: Introductionmentioning
confidence: 99%